Anodic coupling of carboxylic acids to electron-rich double bonds: A surprising non-Kolbe pathway to lactones - Perkins, Robert J.; Xu, Hai-Chao; Campbell, John M.; Moeller, Kevin D. (Beilstein Journal of Organic Chemistry, 2013)
Carboxylic acids have been electro-oxidatively coupled to electron-rich olefins to form lactones. Kolbe decarboxylation does not appear to be a significant competing pathway. Experimental results indicate that oxidation occurs at the olefin and that the reaction proceeds through a radical cation intermediate.
Keywords: carboxylic acid; cyclization; electrolysis; free radical; kolbe; radical cation

(untitled) - Sperry, J. B.; Wright, D. L. (Chem. Soc. Rev., 2006)

(untitled) - Yoshida, J.; Kataoka, K.; Horcajada, R.; Nagaki, A. (Chem. Rev., 2008)

(untitled) - Moeller, K. D. (Synlett, 2009)

(untitled) - Xu, H.-C.; Moeller, K. D. (J. Am. Chem. Soc., 2010)

(untitled) - Sutterer, A.; Moeller, K. D. (J. Am. Chem. Soc., 2000)

(untitled) - Liu, B.; Duan, S.; Sutterer, A. C.; Moeller, K. D. (J. Am. Chem. Soc., 2002)

(untitled) - Brandt, J. D.; Moeller, K. D. (Org. Lett., 2005)

(untitled) - Xu, H.-C.; Brandt, J. D.; Moeller, K. D. (Tetrahedron Lett., 2008)

(untitled) - Campbell, J. M.; Xu, H.-C.; Moeller, K. D. (J. Am. Chem. Soc., 2012)

Organic Electrochemistry - Torii, S.; Tanaka, H. (Carboxylic Acids, 2001)

Electrochemistry IV - Schäfer, H. J. (Recent Contributions of Kolbe Electrolysis to Organic Synthesis, 1990)

(untitled) - Schäfer, H. J. (Chem. Phys. Lipids, 1979)

(untitled) - Lebreux, F.; Buzzo, F.; Markó, I. E. (Synlett, 2008)

(untitled) - Huhtasaari, M.; Schäfer, H. J.; Becking, L. (Angew. Chem., Int. Ed. Engl., 1984)

(untitled) - Matzeit, A.; Schäfer, H. J.; Amatore, C. (Synthesis, 1995)

(untitled) - Scott, A. I.; Dodson, P. A.; McCapra, F.; Meyers, M. B. (J. Am. Chem. Soc., 1963)

(untitled) - Coutts, I. G. C.; Edwards, M.; Musto, D. R.; Richards, D. J. (Tetrahedron Lett., 1980)

(untitled) - Coutts, I. G. C.; Culbert, N. J.; Edwards, M.; Hadfield, J. A.; Musto, D. R.; Pavlidis, V. H.; Richards, D. J. (J. Chem. Soc., Perkin Trans. 1, 1985)

(untitled) - Thomas, H. G.; Schwager, H.-W. (Tetrahedron Lett., 1984)

(untitled) - Deffieux, D.; Fabre, I.; Courseille, C.; Quideau, S. (J. Org. Chem., 2002)

(untitled) - Xu, H.-C.; Moeller, K. D. (Angew. Chem., Int. Ed., 2010)

(untitled) - Xu, G.; Moeller, K. D. (Org. Lett., 2010)

(untitled) - Tang, F.; Moeller, K. D. (Tetrahedron, 2009)